A Rare Case Report of Biloma After Cholecystectomy - FaisalUddin, Mohammed (Cureus, 2019)
Biloma is an encapsulated collection of bile outside or inside the biliary system within the abdominal cavity. It is a rare condition with an incidence of 0.3%-2%. The most common cause of spontaneous biloma is choledocholithiasis, and other causes include abdominal trauma and surgery, bile duct tumors, liver infarction, percutaneous catheter drainage, transhepatic cholangiogram and endoscopic retrograde cholangiopancreatography (ERCP) but the exact cause is yet to be discovered. We herein present a case report of biloma as a complication of laparoscopic cholecystectomy. A 58-year-old male presented to our hospital emergency room with complaints of fever, nausea, vomiting, and pain in the right upper quadrant after six weeks of laparoscopic cholecystectomy for cholecystitis. He was diagnosed with computed tomography (CT) scan quickly, and he has treated with pigtail catheter percutaneous drainage. On a follow-up visit, after four weeks, his abdominal pain had improved and white blood count was also reduced to baseline.